2014
DOI: 10.32607/20758251-2014-6-2-84-94
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Protein Nanodiscs Offer New Perspectives for Structural and Functional Studies of Water-Soluble Membrane-Active Peptides

Abstract: Lipid-protein nanodiscs (LPNs) are nanoscaled fragments of a lipid bilayer stabilized in solution by the apolipoprotein or a special membrane scaffold protein (MSP). In this work, the applicability of LPN-based membrane mimetics in the investigation of water-soluble membrane-active peptides was studied. It was shown that a pore-forming antimicrobial peptide arenicin-2 from marine lugworm (charge of +6) disintegrates LPNs containing both zwitterionic phosphatidylcholine (PC) and anionic phosphatidylglycerol (PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…This presents a nice prospect for the use of LPNs as a membrane mimetic for structural studies of multidomain membrane proteins, especially since LPNs have been shown to be a perfect medium for the refolding of membrane proteins (32). Nanodiscs were first proposed as a reference medium for detergent screening (28) or as a possible environment in which to study the topology of small peptides in the membrane (33)(34)(35)(36); however, recent advances, such as the development of new MSPs that form smaller discoid particles (up to~50 kDa) (31), isotope labeling strategies, and NMR experimental techniques have also made them applicable for structural studies of membrane proteins (37). In this work, we show that a transmembrane protein with a relatively large water-soluble domain (p75-DECD) can be incorporated into LPNs of various sizes and studied by the conventional means of solution NMR spectroscopy to obtain biologically relevant structural data.…”
Section: Nanodiscs As a Versatile Medium For Structural And Functionamentioning
confidence: 98%
“…This presents a nice prospect for the use of LPNs as a membrane mimetic for structural studies of multidomain membrane proteins, especially since LPNs have been shown to be a perfect medium for the refolding of membrane proteins (32). Nanodiscs were first proposed as a reference medium for detergent screening (28) or as a possible environment in which to study the topology of small peptides in the membrane (33)(34)(35)(36); however, recent advances, such as the development of new MSPs that form smaller discoid particles (up to~50 kDa) (31), isotope labeling strategies, and NMR experimental techniques have also made them applicable for structural studies of membrane proteins (37). In this work, we show that a transmembrane protein with a relatively large water-soluble domain (p75-DECD) can be incorporated into LPNs of various sizes and studied by the conventional means of solution NMR spectroscopy to obtain biologically relevant structural data.…”
Section: Nanodiscs As a Versatile Medium For Structural And Functionamentioning
confidence: 98%
“…However, this assembled structure is only stable when a secondary amphiphile is added that can bind to the high curvature edges. In this case, helical lipoproteins called membrane scaffolding proteins (MSPs) have been shown to efficiently bind to the sides of lamellar sheets to generate nanodisc structures that are alone highly stable [196]. This combination of phospholipids and MSPs efficiently coat all sides of a nanoplatelet, with different adsorbates localizing to different regions depending on curvature (Fig.…”
Section: Surface Engineering For Biomedical Applicationsmentioning
confidence: 99%
“…Nanodiscs with different lipid composition have been used to study membrane‐bound active peptides . In a recent work, the authors showed that arenicin‐2, a pore‐forming antimicrobial peptide, disintegrates nanodiscs containing both zwitterionic phosphatidylcholine (PC) and anionic phosphatidylglycerol (PG).…”
Section: Biophysical Studies Of Membrane Proteins In Nanodiscsmentioning
confidence: 99%
“…This is due to the propensity of membrane proteins to aggregate outside a membrane environment during their isolation from membranes using detergents. Therefore, in recent years, several lipid membrane mimics were developed in order to facilitate interrogation of membrane proteins by rigorous biophysical and analytical techniques. In 2002, Sligar and coworkers at the University of Illinois at Urbana‐Champaign developed a new technology termed as nanodiscs based on previous experimentation with ApoA1 and synthetic phospholipids .…”
Section: Introduction To Nanodisc Technologymentioning
confidence: 99%